An Intraarticular Sacroiliac Steroid Injection Under the Guidance of Computed Tomography for Relieving Sacroiliac Joint Pain: A Clinical Outcome Study with Two Years of Follow-Up - Orçun ŞAHİN and Ali HARMAN and Rahmi Can AKGÜN and İsmail Cengiz TUNCAY (Archives of Rheumatology, 2012)
Objectives: The aim of this study was to analyze the effectiveness of an injection of a computed tomography (CT)-guided intraarticular steroid and a local anesthetic for the treatment of sacroiliac joint (SIJ) pain over a two-year follow-up period. Patients and methods: Between January 2009 and December 2011, a total of 46 patients (18 males, 28 females; mean age 52.7 years; range 41 to 65 years) with SIJ pain who were scheduled to undergo an injection with a CT-guided intraarticular steroid and a local anesthetic were included. After properly prepared, the mixture of triamcinolone acetonide 80 mg and bupivacaine hydrochloride 4 cc was injected under CT guidance. The pain was evaluated using the visual analog scale (VAS) before and after the injection. The clinical follow-up was performed the day after the injection as well as at one week, three weeks, and six months and in the last visit. The differences between the VAS scores before and after the injections were analyzed statistically. Results: The mean follow-up was 26.7 months (range 24 to 36 months). Eight out of 46 patients (17.4%) needed a second injection. Five of them (10.8%) failed to show improvement during the follow-up after the intraarticular cortisone injection. The overall success rate of the SIJ injection was 89.2%. The differences between the VAS scores before the injection and at intervals of one day, one week, three weeks, and six months were significantly lower. This response remained significant after a minimum of two years of follow-up with a median VAS score of 20.5 (min-max: 0-87). Conclusion: Sacroiliac joint injections under CT guidance are a sufficient treatment modality for pain and symptom control in patients suffering from pain due to active SIJ pathologies. They are safe and effective and can be used as an alternative treatment of choice for patients with long-term SIJ pain.